2015
DOI: 10.1016/j.humov.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Optimal technique for maximal forward rotating vaults in men’s gymnastics

Abstract: In vaulting a gymnast must generate sufficient linear and angular momentum during the approach and table contact to complete the rotational requirements in the post-flight phase. This study investigated the optimisation of table touchdown conditions and table contact technique for the maximisation of rotation potential for forwards rotating vaults. A planar seven-segment torque-driven computer simulation model of the contact phase in vaulting was evaluated by varying joint torque activation time histories to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Modelling handspring was found with the former horse used for vault 42 and for the current table 39,43 , while was not found for other vault groups. It was veri ed that changing the apparatus from horse to table has changed handspring vertical take-o velocity 13 .…”
Section: Approach Runningmentioning
confidence: 74%
See 3 more Smart Citations
“…Modelling handspring was found with the former horse used for vault 42 and for the current table 39,43 , while was not found for other vault groups. It was veri ed that changing the apparatus from horse to table has changed handspring vertical take-o velocity 13 .…”
Section: Approach Runningmentioning
confidence: 74%
“…Considering velocity, Y et al 47 During table contact, the gymnast interacts with the table to further re ne post ight linear and angular momentum requirements, to achieve the vault's desired distance, height and rotations 24 . e simulations presented in handspring double salto 43 demonstrated that changes in horizontal velocity and contact technique both have an in uence on post-ight rotation potential. is nd reinforces that increasing horizontal approach velocity would improve performance 25 .…”
Section: Approach Runningmentioning
confidence: 96%
See 2 more Smart Citations
“…A straight triple somersault has now been performed in tumbling competition. In gymnastics vaulting it was found that a handspring double somersault with 1½ twists and a handspring triple somersault tucked were limiting vaults (Hiley et al, 2015). A handspring triple tucked somersault vault has now been attempted in competition.…”
Section: Introductionmentioning
confidence: 99%